Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 54074 species occurrences available in GBIF matching the query: { "and" : [ "Country is Belgium", "TaxonKey is one of (Aponogeton distachyos L.f., Cabomba caroliniana A.Gray, Cherax destructor Clark, 1936, Crassula helmsii (Kirk) Cockayne, Egeria densa Planch., Erythranthe guttata (DC.) G.L.Nesom, Faxonius immunis (Hagen, 1870), Faxonius juvenilis (Hagen, 1870), Faxonius rusticus (Girard, 1852), Faxonius virilis (Hagen, 1870), Heracleum mantegazzianum Sommier & Levier, Heracleum persicum Desf. ex Fisch., C.A.Mey. & Avé-Lall., Heracleum sosnowskyi Manden., Houttuynia cordata Thunb., Hydrocotyle ranunculoides L.fil., Impatiens glandulifera Royle, Koenigia polystachya (Wall. ex Meisn.) T.M.Schust. & Reveal, Lagarosiphon major (Ridl.) Moss, Ludwigia grandiflora (Michx.) Greuter & Burdet, Ludwigia peploides (Kunth) P.H.Raven, Lysichiton americanus Hultén & H.St.John, Myriophyllum aquaticum (Vell.) Verdc., Myriophyllum heterophyllum Michx., Petasites japonicus (Siebold & Zucc.) Maxim., Pontederia cordata L., Procambarus acutus (Girard, 1852), Procambarus clarkii (Girard, 1852), Procambarus virginalis Lyko, 2017, Saururus cernuus L., Zizania latifolia (Griseb.) Turcz. ex Stapf)", "OccurrenceStatus is Present" ] } The dataset includes 54074 records from 54 constituent datasets: 1 records from EURISCO, The European Genetic Resources Search Catalogue. 303 records from iNaturalist Research-grade Observations. 6 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 6254 records from DEMNA-DNE : Exotic plant occurrences in Wallonia. 3 records from VIS - Reference freshwater monitoring in Flanders, Belgium (post 2013). 1 records from Biotope cadastre of the open landscapes, Recorder-Lux database. 2857 records from Pl@ntNet automatically identified occurrences. 4191 records from Rat control occurrences collected by VMM in Flanders, Belgium. 27 records from Ecological typology of waterways, vegetation surveys. 1 records from Institut Botanic de Barcelona (IBB, CSIC-Ajuntament de Barcelona), BC-Plantae. 145 records from Pl@ntNet observations. 12 records from INSDC Sequences. 20 records from BioFresh Pond Data. 1 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 9504 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 289 records from Meise Botanic Garden Herbarium (BR). 20 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 5 records from Alien macroinvertebrates in Flanders, Belgium. 5 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL). 368 records from Invasive species - Invasive plants near waterways in West and East Flanders, Belgium. 1 records from bioman_belgium. 5 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 9 records from Natagriwal ; Observations made from operations within Natura 2000 habitats and other semi-natural areas. 24598 records from Waarnemingen.be - Non-native plant occurrences in Flanders and the Brussels Capital Region, Belgium. 15 records from Living plant collection of Meise Botanic Garden. 127 records from Contrat de Rivière - RIPARIAS: detection and management of aquatic invasive alien species. 3 records from RBINS DaRWIN. 100 records from DEMNA-DNE : Exotic animal occurrences in Wallonia, Belgium. 11 records from Naturalis Biodiversity Center (NL) - Botany. 10 records from Manscape. 1397 records from Participatory inventory of the Himalayan balsam within the Dyle basin since 2008. 2 records from Aranzadi Zientzi Elkartea. 1 records from Herbarium Berolinense, Berlin (B). 34 records from Belgian IFBL Flora Checklists (1939-1971). 2 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 6 records from Miscellaneous Vascular Plants. 1 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 198 records from Inland water macrophyte occurrences in Flanders, Belgium. 1 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 3 records from Royal Belgian Institute of Natural Sciences Crustacea collection. 20 records from Herbarium of Namur. 2753 records from Observations.be - Non-native species occurrences in Wallonia, Belgium. 517 records from Waarnemingen.be - Non-native animal occurrences in Flanders and the Brussels Capital Region, Belgium. 1 records from International Barcode of Life project (iBOL). 1 records from Carnet en Ligne. 48 records from N2000-Alien plants along river banks. 3 records from data.mnhn.lu observation data. 10 records from Charles University Prague - Herbarium PRC. 2 records from Collections and observation data National Museum of Natural History Luxembourg. 10 records from VIS - Fishes in inland waters in Flanders, Belgium. 1 records from National Herbarium of Victoria (MEL) AVH data. 162 records from Invasive species - New Zealand pigmyweed (Crassula helmsii) occurrences in Flanders, Belgium. 5 records from VIS - Non-native fish in Flanders, Belgium. 4 records from TestWat - Macroinvertebrates and macrophytes of freshwater bodies in Flanders, Belgium. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences